Evolutionary game model of migraine based on the human brain hypersensitivity - Han, Dong-Gyun (Frontiers in Neurology, 2023)
Based on all studies published up to 2020, the prevalence of migraine worldwide is approximately 14%, although it varies regionally. Despite being one of the most disabling diseases, migraine still exists through natural selection and is prevalent today. This raises the question of what evolutionary advantages have led to the survival of migraine. The ultimate answer to this question should be found in evolution; however, there is no clear explanation yet. Notably, all the genes that cause migraine make the sensory organs and cortex of the migraine sufferer hypersensitive. In a state of hypersensitivity, the brain could recognize external threats easily. Game theory is a useful tool for explaining evolution in terms of genes. Just as the Hawk–Dove game, which has two strategies (aggressive and passive) and four fitness values, an evolutionary game between a migraineur and a non-migraineur, which shows two phenotypes (more sensitive and less sensitive) and four fitness values, can be played if a migraineur quickly recognizes a predator and informs a non-migraineur of its appearance and the non-migraineur later helps the migraineur escape from danger. This study aimed to explore the evolutionary mechanics of migraine that can be modeled. Furthermore, it tried to define why the human brain's hypersensitivity is a prerequisite for developing this evolutionary game model.